2014
DOI: 10.1007/s12275-014-4078-0
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter apis sp. nov., isolated from the intestinal tract of a honey bee, Apis mellifera

Abstract: A novel Gram-negative, obligate aerobic, non-motile, and both coccobacillus- and bacillus-shaped bacterium, designated strain HYN18(T), was isolated from the intestinal tract of a honey bee (Apis mellifera). The isolate was oxidase-negative and catalase-positive. Strain HYN18(T) showed optimum growth at 25°C, pH 6-7, and in the presence of 1% (w/v) NaCl in trypticase soy broth medium. The isolate was negative for hydrolyses of starch, casein, gelatin and urea, indole production from tryptone and hemolysis on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Two species of Acinetobacter have been found as novel species in the nectar of a wild plant in the Mediterranean: Acinetobacter nactaris and Acinetobacter boissieri [86]. Furthermore, Acinetobacter apis has been discovered in the intestinal tract of A. mellifera [87]. Many studies have shown that Acinetobacter species thrive in a sugar-rich habitat and have even formed a symbiosis with the Pae aphid, a phloem sap-eating insect [88].…”
Section: Discussionmentioning
confidence: 99%
“…Two species of Acinetobacter have been found as novel species in the nectar of a wild plant in the Mediterranean: Acinetobacter nactaris and Acinetobacter boissieri [86]. Furthermore, Acinetobacter apis has been discovered in the intestinal tract of A. mellifera [87]. Many studies have shown that Acinetobacter species thrive in a sugar-rich habitat and have even formed a symbiosis with the Pae aphid, a phloem sap-eating insect [88].…”
Section: Discussionmentioning
confidence: 99%
“…The genus Acinetobacter is currently comprised of fifty-five distinct species that have been originally isolated from various sources, such as human clinical specimens, invertebrate and vertebrate animals, vegetables, soil and water [34,35]. Although research on the genus Acinetobacter has been particularly focused on some species that have effects on human health, especially A. baumannii, the beneficial effects of most of the remaining species on their hosts have never been addressed to date.…”
Section: Discussionmentioning
confidence: 99%
“…The only respiratory quinone detected is ubiquinone-9 (Q-9) and Table 3. Phenotypic Characteristics of Ventosimonas gracilis CV58 T compared to other cultivated representatives from the order Pseudomonadales Strains: 1, Ventosimonas gracilis CV58 T ; 2, Pseudomonas aeruginosa ATCC 27853 (G+C content from Fang et al, 2012); 3, Pseudomonas arsenicoxydans VC-1 T (data from Campos et al, 2010); 4, Acinetobacter apis HYN18 T (data from Kim et al, 2014). Substrate usage and enzyme activity were determined using GN2 and GEN III microplates and API 20 NE strips.…”
mentioning
confidence: 99%